Solid-state NMR of vulcanized natural rubber/butadiene rubber blends: Local organization and cross-linking heterogeneities - Pierre Daniel; Cristina Coelho-Diogo; Valérie Gaucher; Grégory Stoclet; Clément Robin; Cédric Lorthioir (Magnetic Resonance Letters)
Elastomer blends, among which natural rubber (NR) and butadiene rubber (BR), are involved in many components of the automotive/tire industry. A comprehensive understanding of their mechanical behavior requires, among other features, a detailed description of the cross-link density in these mixtures. In the case of vulcanized immiscible blends, the distribution of the cross-link density within each of the NR- and BR-rich domains is key information, but difficult to determine using the conventional approaches used for one-component cross-linked elastomers. In this study, the vulcanization within NR/BR blends is investigated using a robust 1H double-quantum (DQ) MAS recoupling experiment, BaBa-xy16. Two kinds of cross-linked NR/BR blends were considered with two different microstructures for the BR component. The bulk organization of the resulting blends was first probed by analyzing the 1H spin-lattice relaxation behavior. In a second step, BaBa-xy16 was used to investigate, in a selective way, the cross-link heterogeneities within NR/BR blends. In particular, for immiscible NR/BR mixtures, the distribution of the cross-link density between both phases was compared and the observed differences were discussed.